STRATEGI PEMASARAN DAN PENGEMBANGAN PRODUK UMKM ULOS DI UD. STEVEN PARDEDE - Dian G Purba; Angelina Simbolon; Yusy Prita Hizkia Purba (CV. Denasya Smart Publisher, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) is an important effort to support the local economy and strengthen the sustainability of local culture. This study explores the marketing strategy and product development of Ulos MSMEs at UD. Steven Pardede, located in jl.Musyawarah No.9 the North Sumatra region, Indonesia. This research uses a qualitative approach by conducting in-depth interviews and direct observations of business owners and related staff. The research results show that UD. Steven Pardede implements a marketing strategy that focuses on strengthening the brand image, increasing product visibility through exhibitions and social media, as well as utilizing partnerships with shops and other companies in distributing their Ulos Batak products. Apart from that, the company also invests in product development through design innovation and product diversification according to market demand. This research provides valuable insight into best practices in marketing and developing Ulos MSME products, as well as highlighting the importance of adapting to market and technological changes in strengthening the competitiveness of MSMEs in the era of globalization. The practical implications of these findings include recommendations for implementing more effective digital marketing strategies and strengthening industry partnerships to support the growth of Ulos MSMEs in local and international markets.